CHARACTERIZATION OF SERBIAN SUNFLOWER HONEYS BY THEIR PHYSICOCHEMICAL CHARACTERISTICS - Živkov Baloš, Milica; Jakšić, Sandra; Popov, Nenad; Polaček, Vladimir (Food and Feed Research, 2021)
Abstract: Five physicochemical parameters (water content, electrical conductivity, total acidity (pH), ash mass fraction and concentration of free acids) were analyzed in 15 sunflower honeys collected from several localities in Vojvodina, Republic of Serbia. The mean values of analyzed honeys were: water content 16.87%; concentration of free acids 27.43 mEq/kg; electrical conductivity 0.34 mS/cm; pH 3.64. The selected physicochemical characteristics of all honey samples from Serbia analyzed in this research can be considered to be within the parameters expected for sunflower honey in general. The values for ash mass fraction, electrical conductivity and concentration of free acids in all sunflower honey samples showed similar trends. High correlation was established between electrical conductivity and ash mass fraction. Statistically significant difference at p≤0.05 (p=0.017) was established only for average values of free acids concentration between honey samples originating from the localities Kanjiža and Čelarevo. All of the analyzed honeys were found to meet national and European legislation for all investigated parameters. Therefore, further research on physicochemical properties of sunflower honey is required to confirm the quality and authenticity of this product and for better understanding the benefits of this honey.
Keywords: sunflower honey; electrical conductivity; acidity; ash